Quantitative Comparison of Bile Acid Distribution and Intestinal Transport from Native Cow-bezoar and Artificial and in vitro Cultured Substitutes using Caco-2 Cell Monolayer Model - Ying CHEN; Xiao-Ru HU; Xian-Long CHENG; Shuang-Cheng MA; Qing-Sen RAN; Qing YANG; Wei-Jie QIANG; Zhong DAI; Xiao-Xin ZHU (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Objective This study was conducted to examine the absorption and translocation of conjugated bile acids (BAs) in Calculus bovis and its substitutes to detect differences in these materials.Methods A Caco-2 monolayer cell model was used to compare the apparent permeability coefficient (Papp) value and efflux ratio (ER) of BAs in natural cow-bezoar (NCB), artificial cow-bezoar (ACB), and in vitro cultured cow-bezoar (Ivt-CCB). Papp and ER values were determined by liquid chromatography-mass spectrometry. Samples were separated on an analytical column.Results The distribution of BAs in NCB was significantly different from that in ACB and Ivt-CCB. The percentages of conjugated BAs were significantly higher in NCB than in the two substitutes. The distribution differences of conjugated and unconjugated BAs can be used to distinguish costly NCB from relatively inexpensive substitutes.Conclusion The transport characteristics of BAs in Ivt-CCB were more consistent with NCB than with ACB, even when the proportions of BAs in Ivt-CCB were closer to those of ACB. Keywords: Bile acids, Cow-bezoar, Intestinal transport, Caco-2 cell, Apparent permeability coefficient value, Efflux ratio